Active and Morphing Aerospace Structures–A Synthesis between Advanced Materials, Structures and Mechanisms - Baier, Horst; Datashvili, Leri (International journal of aeronautical and space sciences, 2011)
Active and shape morphing aerospace structures are discussed with a focus on activities aimed at practical implementation. In active structures applications range from dynamic load alleviation in aircraft and spacecraft up to static and dynamic shape control. In contrast, shape morphing means strong shape variation according to different mission status and needs, aiming to enhance functionality and performance over wide flight and mission regimes. The interaction of required flexible materials with the morphing structure and the actuating mechanisms is specifically addressed together with approaches in design and simulation. KCI Citation Count: 1